Numerical modelling and experimental validation of laminar flame flashback in tube burners for H2-enriched methane-air combustion - Zeb, Muhammad Kamran; Muelas, Alvaro; Ballester, Javier (Jornada de Jóvenes Investigadores del I3A, 2025)
The propagation of the flame upstream of its stable location in burners (i.e., flame flashback) is probably the main challenge in hydrogen combustion. Thus, the laminar flashback velocity of H2-CH4/Air flames is studied using experiments and CFD. The effect of changing the velocity profile is studied using a cylindrical inset, lowering the wall velocity gradient. An increased flashback resistance was observed for 60% H2 enrichment. Results suggest core flow flashback rather than boundary layer flashback (as initially expected), which is confirmed by CFD